Binder composition for secondary battery and electrode mixture
A core-shell structured binder composition for lithium secondary batteries addresses bonding issues and electrolyte swelling, improving adhesive strength and structural stability to enhance battery performance.
Patent Information
- Application Number
- JP2023532618
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-18
- Filing Date
- 2021-12-17
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2041-12-17
AI Technical Summary
Lithium secondary batteries face issues with loose bonds between electrode active materials and current collectors due to repeated charging and discharging, leading to increased contact resistance and reduced battery capacity, along with swelling caused by electrolyte decomposition, which compromises structural stability.
A binder composition for secondary batteries featuring core-shell structured emulsion polymer particles with specific ratios of unsaturated carboxylic acid monomers in the core and shell, enhancing binding strength and maintaining electrode stability during charge/discharge cycles.
The binder composition improves adhesive strength, reduces electrode expansion, and suppresses electrolyte swelling, thereby maintaining structural integrity and enhancing battery performance.
Smart Images

Figure 0007618343000001
Abstract
Description
[Technical field]
[0001] Cross-reference to related application(s) This application claims the benefit of priority based on Korean Patent Application No. 10-2020-0178282 filed on December 18, 2020, and all contents disclosed in the documents of said Korean patent application are incorporated herein by reference.
[0002] The present invention relates to a binder composition for a secondary battery and an electrode mixture containing the same. [Background technology]
[0003] 2. Description of the Related Art With the rapid increase in the use of fossil fuels, there is an increasing demand for the use of alternative and renewable energy. As part of this, the field in which research is most active is the field of secondary batteries that utilize electrochemistry.
[0004] Recently, with the increasing technological development and demand for portable devices such as portable computers, portable phones, and cameras, the demand for secondary batteries as energy sources has increased rapidly. Among such secondary batteries, lithium secondary batteries, which have high energy density and working potential, long cycle life, and low self-discharge rate, have been much researched and are now commercially available and in wide use.
[0005] In addition, as interest in environmental issues grows, much research is being conducted into electric vehicles and hybrid vehicles that can replace fossil fuel engines, which are one of the main causes of air pollution, and lithium secondary batteries are also used as a power source for such electric vehicles and hybrid vehicles.
[0006] In lithium secondary batteries, lithium transition metal oxides are generally used as the positive electrode active material, and graphite-based materials are generally used as the negative electrode active material. Electrodes for lithium secondary batteries are manufactured by mixing such active materials and binder components, dispersing them in a solvent to form a slurry, and then applying the slurry to the surface of a current collector to form a mixture layer.
[0007] In general, lithium secondary batteries are charged and discharged by repeatedly inserting and desorbing lithium ions from the positive electrode into and from the negative electrode. During this repetitive process, the bonds between the electrode active materials or conductive materials become loose, increasing the contact resistance between the particles and the resistance of the electrode itself.
[0008] Therefore, the binder used in the electrode must be capable of maintaining excellent binding strength between the electrode active material and the current collector, while also being capable of buffering against expansion and contraction of the electrode active material due to insertion and desorption of lithium ions in the electrode.
[0009] In particular, in recent years, in order to increase the discharge capacity of the electrode, natural graphite, which has a theoretical discharge capacity of 372 mAh / g, is often combined with materials with large discharge capacities, such as silicon, tin, and silicon-tin alloys. However, as a result of this, the volume expansion rate of the material increases significantly as charging and discharging are repeated, which causes the anode material to detach, resulting in a rapid decrease in battery capacity and a shortened lifespan.
[0010] In addition, lithium-ion batteries may experience a swelling phenomenon in which the battery expands due to gas generated during decomposition of the electrolyte inside the battery. If the temperature of the battery rises during use of electronic products, the decomposition of the electrolyte is promoted, accelerating the swelling phenomenon and causing a problem of reduced battery stability.
[0011] Therefore, there is a pressing need for research into binders and electrode materials that can achieve excellent binding strength to such an extent that separation between electrode active materials or between the electrode active material and the current collector can be prevented, and that can maintain the structural stability of the electrode even during repeated charge / discharge cycles. Summary of the Invention [Problem to be solved by the invention]
[0012] The present invention aims to provide a binder composition for a secondary battery, which has excellent properties such as binding strength and mechanical properties, and can maintain the structural stability of an electrode even during repeated charge-discharge cycles.
[0013] Another object of the present specification is to provide a secondary battery electrode mixture containing the binder composition for secondary batteries.
[0014] Another object of the present specification is to provide a secondary battery electrode containing the secondary battery electrode mixture.
[0015] Another object of the present specification is to provide a secondary battery including the secondary battery electrode. [Means for solving the problem]
[0016] According to one aspect of the present invention, there is provided a binder composition for a secondary battery, comprising emulsion polymer particles having a core-shell structure, the emulsion polymer particles satisfying the following relational formula 1 and having a surface acidity value of 0.15 to 2.0 mmol / g: [Equation 1] AC-Core <AC-Shell
[0017] In the above formula, AC-Core is the relative content (wt%) of the repeating unit derived from the unsaturated carboxylic acid monomer in the core of the emulsion polymer particle, and AC-Shell is the relative content (wt%) of the repeating unit derived from the unsaturated carboxylic acid monomer in the shell of the emulsion polymer particle.
[0018] More specifically, the binder composition for a secondary battery may satisfy the following Relational Formula 2. [Equation 2] 2 x AC-Core <AC-Shell
[0019] In the above formula, AC-Core is the relative content (wt%) of the repeating unit derived from the unsaturated carboxylic acid monomer in the core of the emulsion polymer particle, and AC-Shell is the relative content (wt%) of the repeating unit derived from the unsaturated carboxylic acid monomer in the shell of the emulsion polymer particle.
[0020] According to one embodiment of the invention, the core of the emulsion polymer particle may include a repeating unit derived from a conjugated diene monomer, a repeating unit derived from an aromatic vinyl monomer, a repeating unit derived from an alkyl (meth)acrylate monomer, and a repeating unit derived from an unsaturated carboxylic acid monomer.
[0021] In this case, the core of the emulsion polymer particle may contain about 50 to about 100 parts by weight of the repeating unit derived from the aromatic vinyl monomer, based on 100 parts by weight of the repeating unit derived from the conjugated diene monomer, and the lower limit may be about 50 parts by weight or more, about 60 parts by weight or more, or about 65 parts by weight or more, and the upper limit may be about 100 parts by weight or less, about 90 parts by weight or less, or about 80 parts by weight or less.
[0022] The core of the emulsion polymer particle may contain about 5 to about 50 parts by weight of the repeating unit derived from the alkyl (meth)acrylate monomer, relative to 100 parts by weight of the repeating unit derived from the conjugated diene monomer, and the lower limit may be about 5 parts by weight or more, about 10 parts by weight or more, or about 15 parts by weight or more, and the upper limit may be about 50 parts by weight or less, about 40 parts by weight or less, or about 30 parts by weight or less.
[0023] The core of the emulsion polymer particle may contain about 1 to about 20 parts by weight of the repeating unit derived from the unsaturated carboxylic acid monomer relative to 100 parts by weight of the repeating unit derived from the conjugated diene monomer, the lower limit of which may be about 1 part by weight or more, about 5 parts by weight or more, or about 8 parts by weight or more, and the upper limit of which may be about 20 parts by weight or less, about 15 parts by weight or less, or about 12 parts by weight or less.
[0024] According to another embodiment of the present invention, the shell of the emulsion polymer particle may include a repeating unit derived from an alkyl (meth)acrylate monomer and a repeating unit derived from an unsaturated carboxylic acid monomer.
[0025] In this case, the shell of the emulsion polymer particles may contain about 5 to about 100 parts by weight of the repeating unit derived from the unsaturated carboxylic acid monomer, based on 100 parts by weight of the repeating unit derived from the alkyl (meth)acrylate monomer, and the lower limit may be about 5 parts by weight or more, about 7 parts by weight or more, or about 10 parts by weight or more, and the upper limit may be about 100 parts by weight or less, about 80 parts by weight or less, or about 70 parts by weight or less.
[0026] In this case, the shell of the emulsion polymer particle may further include about 5 to about 70 parts by weight of a repeating unit derived from an aromatic vinyl monomer, based on 100 parts by weight of the repeating unit derived from the alkyl (meth)acrylate monomer, the lower limit of which may be about 5 parts by weight or more, about 10 parts by weight or more, or about 15 parts by weight or more, and the upper limit of which may be about 70 parts by weight or less, about 50 parts by weight or less, or about 40 parts by weight or less.
[0027] Representative examples of the conjugated diene monomer include one or more selected from the group consisting of 1,3-butadiene, isoprene, chloroprene, and piperylene, and preferably 1,3-butadiene.
[0028] The alkyl (meth)acrylate monomer may include at least one selected from the group consisting of methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, n-amyl acrylate, isoamyl acrylate, n-ethylhexyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, n-amyl methacrylate, isoamyl methacrylate, n-hexyl methacrylate, n-ethylhexyl methacrylate, 2-ethylhexyl methacrylate, lauryl acrylate, cetyl acrylate, stearyl acrylate, lauryl methacrylate, cetyl methacrylate, and stearyl methacrylate.
[0029] The aromatic vinyl monomer may include at least one selected from the group consisting of styrene, α-methylstyrene, β-methylstyrene, pt-butylstyrene, chlorostyrene, vinylbenzoic acid, methyl vinylbenzoate, vinylnaphthalene, chloromethylstyrene, hydroxymethylstyrene, and divinylbenzene.
[0030] The unsaturated carboxylic acid monomer may include at least one selected from the group consisting of acrylic acid, methacrylic acid, maleic acid, fumaric acid, glutaric acid, itaconic acid, tetrahydrophthalic acid, crotonic acid, isocrotonic acid, and nadic acid.
[0031] And the shell of the emulsion polymer particles may include crosslinks formed by a crosslinking agent.
[0032] In this case, the crosslinking agent may be a compound containing both an acryloyl group and an ethylenically unsaturated bond in the molecule.
[0033] According to one embodiment of the invention, the weight ratio of the repeating units derived from the unsaturated carboxylic acid monomer present on the surface of the emulsion polymer particles to the total weight of the emulsion polymer particles may be about 2 wt% or more, preferably about 2.5 wt% or more, or about 3 wt% or more, and may be about 20 wt% or less, or about 17 wt% or less, or about 15 wt% or less.
[0034] According to one embodiment of the invention, the emulsion polymer particles may have a relative content of repeat units derived from an unsaturated carboxylic acid monomer of about 5 wt % or more, preferably about 6 wt % or more, or about 20 wt % or less, or about 15 wt % or less, based on the total weight including the core and shell.
[0035] The binder composition for a secondary battery has an electrolyte impregnation rate of 200% or less, specifically, the lower limit is about 1% or more, alternatively about 10% or more, or alternatively about 30% or more, and the upper limit is about 200% or less, alternatively about 170% or less, alternatively about 150% or less, alternatively about 100% or less, or alternatively about 70% or less.
[0036] The emulsion polymer particles may have a surface acidity value of about 0.15 to about 2.0 mmol / g, or about 0.15 mmol / g or more, or about 0.2 mmol / g or more, or about 0.3 mmol / g or more, or about 2.0 mmol / g or less, or about 1.5 mmol / g or less.
[0037] Meanwhile, according to another aspect of the present invention, there is provided a secondary battery electrode mixture comprising the above-mentioned binder composition for secondary batteries and an electrode active material.
[0038] In this case, the secondary battery electrode mixture may further include a conductive material.
[0039] Meanwhile, according to another aspect of the present invention, there is provided a secondary battery electrode including: an electrode mixture layer containing the above-mentioned secondary battery electrode mixture; and an electrode current collector.
[0040] Meanwhile, according to another aspect of the present invention, there is provided a secondary battery including the above-mentioned secondary battery electrode.
[0041] In the present invention, the terms "first", "second", etc. are used to describe various components, and the terms are used only for the purpose of distinguishing one component from another component.
[0042] Furthermore, the terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the present invention.
[0043] A singular expression includes a plural expression unless the context clearly indicates otherwise.
[0044] In this specification, the terms "including," "comprising," or "having" are intended to describe embodied features, numbers, steps, components, or combinations thereof, and do not exclude the possibility of one or more other features, numbers, steps, components, combinations or additional features.
[0045] In addition, in this specification, when a layer or element is referred to as being formed "on" another layer or element, this means that the layer or element is formed directly on the other layer or element, or that other layers or elements may be additionally formed between the layers, on the object, or on the substrate.
[0046] The present invention can be modified in various ways and can have various forms, and will be described in detail below by taking specific embodiments as examples. However, it should be understood that the present invention is not limited to the specific disclosed embodiments, but includes all modifications, equivalents, and alternatives within the spirit and technical scope of the present invention.
[0047] The present invention will be described in detail below.
[0048] First, according to one aspect of the present invention, there is provided a binder composition for a secondary battery, comprising emulsion polymer particles having a core-shell structure, the emulsion polymer particles satisfying the following relational formula 1 and having a surface acidity value of 0.15 to 2.0 mmol / g: [Equation 1] AC-Core <AC-Shell
[0049] In the above formula, AC-Core is the relative content (wt%) of the repeating unit derived from the unsaturated carboxylic acid monomer in the core of the emulsion polymer particle, and AC-Shell is the relative content (wt%) of the repeating unit derived from the unsaturated carboxylic acid monomer in the shell of the emulsion polymer particle.
[0050] The inventors of the present invention have discovered that in a binder composition for secondary batteries including an emulsion of emulsion polymer particles (latex particles) prepared by emulsion polymerization of an acrylate monomer, when the latex particles are prepared to have a core-shell structure and the amount of unsaturated carboxylic acid monomer used in each of the processes for preparing the core and shell is adjusted to satisfy the above-mentioned Relational Formula 1, the adhesive strength of the binder is significantly improved, preventing detachment between electrode active materials or between the electrode active material and the current collector, and achieving stable binding, thereby completing the present invention.
[0051] The binder composition for a secondary battery according to one embodiment of the present invention includes emulsion polymer particles, i.e., latex particles, of specific monomers, and each monomer may be present in each latex particle in the form of a repeat unit derived from the monomer.
[0052] Monomer First, the latex particles may have a core-shell structure as described above, and such latex particles may be prepared by separately carrying out a first polymerization step for forming a core and a second polymerization step for forming a shell. At this time, it is preferable that the core and the shell are composed of different components, taking into consideration the particle stability and the properties as a battery binder, which will be described later.
[0053] core A conjugated diene monomer is used in the first emulsion polymerization for producing the core of the latex particle, and therefore the core of the latex particle contains repeat units derived from the conjugated diene monomer.
[0054] When such a conjugated diene monomer is included as a component of latex particles, the binder produced thereby can suppress electrolyte swelling at high temperatures and has elasticity due to the rubber component, thereby reducing the thickness of the electrode and reducing gas generation, as well as improving adhesion so that the binding force between the electrode active material and the current collector can be maintained.
[0055] Representative examples of the conjugated diene monomer include at least one selected from the group consisting of 1,3-butadiene, isoprene, chloroprene, and piperylene, and preferably 1,3-butadiene.
[0056] In addition, an aromatic vinyl monomer may be further used in the first emulsion polymerization for producing the core of the latex particle, and therefore, the latex particle may further include a repeating unit derived from the aromatic vinyl monomer.
[0057] The aromatic vinyl monomer may be one or more monomers selected from the group consisting of styrene, α-methylstyrene, β-methylstyrene, pt-butylstyrene, chlorostyrene, vinylbenzoic acid, methyl vinylbenzoate, vinylnaphthalene, chloromethylstyrene, hydroxymethylstyrene, and divinylbenzene, and may be preferably styrene.
[0058] In this case, the core of the emulsion polymer particle may contain about 50 to about 100 parts by weight of the repeating unit derived from the aromatic vinyl monomer, based on 100 parts by weight of the repeating unit derived from the conjugated diene monomer, and the lower limit may be about 50 parts by weight or more, about 60 parts by weight or more, or about 65 parts by weight or more, and the upper limit may be about 100 parts by weight or less, about 90 parts by weight or less, or about 80 parts by weight or less.
[0059] In addition, an alkyl(meth)acrylate monomer may be further used in the first emulsion polymerization for producing the core of the latex particle, and therefore, the core of the latex particle may further include a repeating unit derived from the alkyl(meth)acrylate monomer.
[0060] When an alkyl(meth)acrylate monomer is used, the manufactured electrode has a relatively high degree of swelling, so that the resistance of the electrode can be reduced and the ion conductivity can be increased.
[0061] The alkyl (meth)acrylate monomer may include at least one selected from the group consisting of methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, n-amyl acrylate, isoamyl acrylate, n-ethylhexyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, n-amyl methacrylate, isoamyl methacrylate, n-hexyl methacrylate, n-ethylhexyl methacrylate, 2-ethylhexyl methacrylate, lauryl acrylate, cetyl acrylate, stearyl acrylate, lauryl methacrylate, cetyl methacrylate, and stearyl methacrylate.
[0062] The core of the emulsion polymer particle may contain about 5 to about 50 parts by weight of the repeating unit derived from the alkyl (meth)acrylate monomer, relative to 100 parts by weight of the repeating unit derived from the conjugated diene monomer, and the lower limit may be about 5 parts by weight or more, about 10 parts by weight or more, or about 15 parts by weight or more, and the upper limit may be about 50 parts by weight or less, about 40 parts by weight or less, or about 30 parts by weight or less.
[0063] In addition, an unsaturated carboxylic acid monomer may be further used in the first emulsion polymerization for producing the core of the latex particle, and therefore, the core of the latex particle may further include a repeating unit derived from the unsaturated carboxylic acid monomer.
[0064] The unsaturated carboxylic acid monomer may include at least one selected from the group consisting of acrylic acid, methacrylic acid, maleic acid, fumaric acid, glutaric acid, itaconic acid, tetrahydrophthalic acid, crotonic acid, isocrotonic acid, and nadic acid.
[0065] The core of the emulsion polymer particle may contain about 1 to about 20 parts by weight of the repeating unit derived from the unsaturated carboxylic acid monomer relative to 100 parts by weight of the repeating unit derived from the conjugated diene monomer, the lower limit of which may be about 1 part by weight or more, about 5 parts by weight or more, or about 8 parts by weight or more, and the upper limit of which may be about 20 parts by weight or less, about 15 parts by weight or less, or about 12 parts by weight or less.
[0066] When the unsaturated carboxylic acid monomer is used in an excessive amount, a problem of increased generation of aggregates during polymerization may occur, and when the unsaturated carboxylic acid monomer is used in an excessively small amount, a problem of increased electrolyte impregnation of the binder to be prepared later may occur.
[0067] In addition, a hydroxyalkyl (meth)acrylate monomer may be further used in the emulsion polymerization for producing the latex particles, and therefore, the latex particles may include repeat units derived from such a monomer.
[0068] shell An alkyl (meth)acrylate monomer is used in the second emulsion polymerization to produce the shell of the latex particle, and therefore the shell of the latex particle contains repeat units derived from the alkyl (meth)acrylate monomer.
[0069] The specific details of the alkyl (meth)acrylate monomer are as described above.
[0070] In addition, an unsaturated carboxylic acid monomer may be further used in the second emulsion polymerization for producing the shell of the latex particle, and therefore, the shell of the latex particle may further include a repeating unit derived from the unsaturated carboxylic acid monomer.
[0071] The specific details of the unsaturated carboxylic acid monomer are as described above.
[0072] The shell of the emulsion polymer particle may contain about 5 to about 100 parts by weight of the repeating unit derived from the unsaturated carboxylic acid monomer, relative to 100 parts by weight of the repeating unit derived from the alkyl (meth)acrylate monomer, and the lower limit may be about 5 parts by weight or more, about 10 parts by weight or more, or about 12 parts by weight or more, and the upper limit may be about 100 parts by weight or less, about 80 parts by weight or less, or about 70 parts by weight or less.
[0073] When the unsaturated carboxylic acid monomer is used in an excessive amount, a problem of increased generation of aggregates during polymerization may occur, and when the unsaturated carboxylic acid monomer is used in an excessively small amount, a problem of increased electrolyte impregnation of the binder to be prepared later may occur.
[0074] In addition, an aromatic vinyl monomer may be further used in the second emulsion polymerization for producing the shell of the latex particle, and therefore, the shell of the latex particle may further include a repeating unit derived from the aromatic vinyl monomer.
[0075] The specific details of the aromatic vinyl monomer are as described above.
[0076] In this case, the shell of the emulsion polymer particle may contain about 5 to about 70 parts by weight of the repeating unit derived from the aromatic vinyl monomer based on 100 parts by weight of the repeating unit derived from the alkyl (meth)acrylate monomer, and the lower limit may be about 5 parts by weight or more, about 10 parts by weight or more, or about 15 parts by weight or more, and the upper limit may be about 70 parts by weight or less, about 50 parts by weight or less, or about 40 parts by weight or less.
[0077] In addition, a crosslinking agent may be further used in the second emulsion polymerization for producing the shell of the latex particles, so that the shell of the emulsion polymer particles may include crosslinks formed by the crosslinking agent.
[0078] Such a crosslinking agent may be a compound containing both an acryloyl group and an ethylenically unsaturated bond in the molecule, and more specifically, it may be allyl (meth)acrylate.
[0079] Such crosslinking agents may be used in the shell of the latex particles produced, resulting in greater particle stability.
[0080] When the crosslinking agent is used, it can be used in an amount of about 0.01 to about 5 parts by weight, or about 0.05 to about 1 part by weight, per 100 parts by weight of the total monomer components contained in the shell.
[0081] Emulsion Polymerization Such latex particles can be produced by a commonly known emulsion polymerization method, and as described above, are produced in a core-shell form. To produce latex particles in a core-shell form, the emulsion polymerization can be carried out at least twice, by a first emulsion polymerization to form a core and a second emulsion polymerization to form a shell surrounding the surface of the core.
[0082] In this case, the polymerization temperature and polymerization time in each of the first and second emulsion polymerizations can be appropriately determined depending on the case. For example, the polymerization temperature can be about 50° C. to about 200° C., or about 50° C. to about 100° C., and the polymerization time can be about 0.5 hours to about 20 hours, or about 1 hour to about 10 hours.
[0083] The polymerization initiator usable in the emulsion polymerization may be an inorganic or organic peroxide. For example, a water-soluble initiator including potassium persulfate, sodium persulfate, ammonium persulfate, etc., and an oil-soluble initiator including cumene hydroperoxide, benzoyl peroxide, etc. may be used.
[0084] In addition, an activator may be further included to promote the initiation of the peroxide reaction together with the polymerization initiator. As the activator, at least one selected from the group consisting of sodium formaldehyde sulfoxylate, sodium ethylenediaminetetraacetate, ferrous sulfate, and dextrose may be used.
[0085] The emulsifier used in the emulsion polymerization includes one or more emulsifiers selected from the group consisting of anionic emulsifiers, cationic emulsifiers, and nonionic emulsifiers.
[0086] Such emulsifiers are materials that have both hydrophilic and hydrophobic groups, and form a micelle structure during emulsion polymerization, allowing the polymerization of each monomer to occur within the micelle structure.
[0087] Emulsifiers commonly used in emulsion polymerization can be classified into anionic emulsifiers, cationic emulsifiers, nonionic emulsifiers, etc., and may be used in combination of two or more kinds in terms of polymerization stability in emulsion polymerization.
[0088] Specific examples of the anionic emulsifier include sodium dodecyl diphenyl ether disulfonate, sodium polyoxyethylene alkyl ether sulfate, sodium lauryl sulfate, sodium dodecyl benzene sulfonate, and dioctyl sodium sulfosuccinate.
[0089] The nonionic emulsifier may be polyethylene oxide alkyl aryl ether, polyethylene oxide alkyl amine, or polyethylene oxide alkyl ester, which may be used alone or in combination of two or more. This may be more effective than a combination of an anionic emulsifier and a nonionic emulsifier, but the present invention is not necessarily limited to these types of emulsifiers.
[0090] The emulsifier can be used in an amount of, for example, about 0.01 to about 10 parts by weight, about 0.05 to about 10 parts by weight, about 0.05 to about 7 parts by weight, or about 0.1 to about 5 parts by weight, per 100 parts by weight of the total monomer components used in producing the latex particles.
[0091] If an excessive amount of emulsifier is used, the particle size of the latex particles becomes small, which may cause a problem of reducing the adhesive strength of the binder. If an excessively small amount of emulsifier is used, the stability of the polymerization in the emulsion polymerization reaction may decrease, which may cause a problem of reducing the stability of the resulting latex particles.
[0092] Meanwhile, as described above, the latex particles contained in the binder composition for a secondary battery according to one aspect of the present invention have a core-shell structure and satisfy the following Relational Formula 1. [Equation 1] AC-Core <AC-Shell
[0093] In the above formula, AC-Core is the relative content (wt%) of the repeating unit derived from the unsaturated carboxylic acid monomer in the core of the emulsion polymer particle, and AC-Shell is the relative content (wt%) of the repeating unit derived from the unsaturated carboxylic acid monomer in the shell of the emulsion polymer particle.
[0094] In other words, the latex particles contained in the binder composition for a secondary battery according to one aspect of the present invention are characterized in that the contents of the repeating units derived from the unsaturated carboxylic acid monomer in each of the core and the shell are different from each other, and the relative content (wt%) of the repeating units derived from the unsaturated carboxylic acid monomer in the shell, i.e., the ratio of the repeating units derived from the unsaturated carboxylic acid monomer to the total repeating units derived from the monomers contained in the shell, is greater than the relative content (wt%) of the repeating units derived from the unsaturated carboxylic acid monomer in the core, i.e., the ratio of the repeating units derived from the unsaturated carboxylic acid monomer to the total repeating units derived from the monomers contained in the core.
[0095] More specifically, the binder composition for a secondary battery may satisfy the following Relational Formula 2. [Equation 2] 2 x AC-Core <AC-Shell
[0096] In the above formula, AC-Core is the relative content (wt%) of the repeating unit derived from the unsaturated carboxylic acid monomer in the core of the emulsion polymer particle, and AC-Shell is the relative content (wt%) of the repeating unit derived from the unsaturated carboxylic acid monomer in the shell of the emulsion polymer particle.
[0097] In other words, the latex particles included in the binder composition for a secondary battery according to an embodiment of the present invention are characterized in that the relative content (wt%) of the repeating units derived from an unsaturated carboxylic acid monomer in the shell, i.e., the ratio of the repeating units derived from an unsaturated carboxylic acid monomer to the total repeating units derived from the monomers included in the shell, is more than twice as large as the relative content (wt%) of the repeating units derived from an unsaturated carboxylic acid monomer in the core, i.e., the ratio of the repeating units derived from an unsaturated carboxylic acid monomer to the total repeating units derived from the monomers included in the core.
[0098] Unsaturated carboxylic acid monomers are characterized by high polarity due to the presence of carboxyl groups. When such unsaturated carboxylic acid monomers are used as binder components, the surface of the binder produced can prevent bonding between the electrode and the electrolyte, thereby suppressing electrode expansion.
[0099] However, when emulsion polymerization is carried out with a high content of such polar monomers, the generation of aggregates increases due to the difference in polymerization rate between the monomers, which makes it difficult to control the polymerization reaction.
[0100] However, according to one embodiment of the present invention, a core-shell structure is produced by two polymerizations, and a relatively small amount of unsaturated carboxylic acid monomer is used in the first polymerization to stably form the core of the latex particle, while a relatively large amount of unsaturated carboxylic acid monomer is used in the second polymerization to increase the ratio of carboxyl groups on the particle surface, thereby achieving the above-mentioned advantageous effects.
[0101] Therefore, in order to produce latex particles having such a core-shell structure, it is necessary to adjust the amount of each monomer used in the first and second emulsion polymerizations.
[0102] For example, the total amount of monomers used in the first emulsion polymerization, i.e., the amount of the conjugated diene monomer, the alkyl (meth)acrylate monomer, the aromatic vinyl monomer, and the unsaturated carboxylic acid monomer, is directly reflected in the content of the repeating unit in the latex particle core unless there are special circumstances, and therefore the relative content of each repeating unit in the latex particle core can be controlled through the relative amount of each monomer used.
[0103] Specifically, the relative amount (wt%) of the unsaturated carboxylic acid monomer among the total monomers used in the first emulsion polymerization to prepare the core, i.e., the conjugated diene monomer, the alkyl (meth)acrylate monomer, the aromatic vinyl monomer, and the unsaturated carboxylic acid monomer, can be adjusted to be greater than the relative amount (wt%) of the unsaturated carboxylic acid monomer among the total monomers used in the second emulsion polymerization to prepare the shell, i.e., the alkyl (meth)acrylate monomer, the aromatic vinyl monomer, and the unsaturated carboxylic acid monomer.
[0104] More preferably, the relative amount (wt%) of the unsaturated carboxylic acid monomer among the total monomers used in the second emulsion polymerization to prepare the shell, i.e., the relative amount (wt%) of the unsaturated carboxylic acid monomer among the total monomers used in the first emulsion polymerization to prepare the core, i.e., the conjugated diene monomer, the alkyl (meth)acrylate monomer, the aromatic vinyl monomer, and the unsaturated carboxylic acid monomer, is adjusted to be at least two times larger than the relative amount (wt%) of the unsaturated carboxylic acid monomer among the total monomers used in the first emulsion polymerization to prepare the core, i.e., the conjugated diene monomer, the alkyl (meth)acrylate monomer, the aromatic vinyl monomer, and the unsaturated carboxylic acid monomer.
[0105] The latex particles may have a core:shell weight ratio of about 8:2 to about 6:4.
[0106] The latex particles may have an intensity average particle size (Di) of about 50 to about 200 nm.
[0107] By adjusting the amount of the monomer used as described above, the relative content (wt%) of the repeating units derived from the unsaturated carboxylic acid monomer in the emulsion polymer particles, i.e., in the entire core and shell of the emulsion polymer particles, may be about 1 to about 20 wt%, or about 1 wt% or more, or about 3 wt% or more, or about 5 wt% or more, or about 9 wt% or more, and may be about 20 wt% or less, or about 17 wt% or less, or about 15 wt% or less.
[0108] According to one embodiment of the invention, the weight ratio of the repeating units derived from the unsaturated carboxylic acid monomer present on the surface of the emulsion polymer particles to the total weight of the emulsion polymer particles may be about 2 wt% or more, preferably about 2.5 wt% or more, or about 3 wt% or more, and may be about 20 wt% or less, or about 17 wt% or less, or about 15 wt% or less.
[0109] The weight ratio of the repeating units derived from the unsaturated carboxylic acid monomer present on the surface of the emulsion polymer particles to the total weight of the emulsion polymer particles can be determined by measuring the change in electrical conductivity value while dropping an aqueous base solution using direct conductometric titration to calculate the number of moles of carboxyl groups distributed on the surface of the latex particles, calculating the weight of the repeating units derived from the unsaturated carboxylic acid monomer distributed on the surface of the latex particles from the calculated weight, and then calculating the weight ratio (wt%) to the total weight of the latex particles including the core and the shell.
[0110] The above ratio indicates the ratio of repeating units derived from unsaturated carboxylic acid monomers actually located on the surface of the emulsion polymer particles, and may be different from the ratio of unsaturated carboxylic acid monomers used in core polymerization or shell polymerization of the emulsion polymer particles. This is significant in that it indicates the ratio of repeating units derived from surface unsaturated carboxylic acid monomers that can actually change the surface properties of the latex particles.
[0111] Specifically, in the case of emulsion polymer particles that do not have a core-shell structure, acid monomers with high polarity during emulsion polymerization may concentrate at the interface between the polymer and the polymerization solution such as water. Therefore, when considering the amount of unsaturated carboxylic acid monomer actually used in emulsion polymerization, a repeating unit derived from the unsaturated carboxylic acid monomer is located on the surface of the emulsion polymer at a higher ratio than would be expected, resulting in a value different from that of the core-shell emulsion polymer particles of the present invention.
[0112] When the weight ratio of the repeating units derived from the unsaturated carboxylic acid monomer present on the surface of the emulsion polymer particles is too high, agglomerations may occur, and problems such as increased electrolyte impregnation may occur. When the weight ratio of the repeating units derived from the unsaturated carboxylic acid monomer present on the surface of the emulsion polymer particles is too low, problems such as reduced stability of the emulsion polymer particles and disintegration of the particles in the electrolyte may occur.
[0113] According to one embodiment of the invention, the emulsion polymer particles may have a relative content of repeat units derived from an unsaturated carboxylic acid monomer of about 5 wt % or more, preferably about 6 wt % or more, or about 20 wt % or less, or about 15 wt % or less, based on the total weight including the core and the shell.
[0114] If the total content of the repeating units derived from the unsaturated carboxylic acid monomer is too low or too high, the impregnation with the electrolyte may be increased, and the particle shape may not be maintained in the electrolyte.
[0115] The emulsion polymer particles may have a surface acidity value of about 0.15 to about 2.0 mmol / g, or about 0.15 mmol / g or more, or about 0.2 mmol / g or more, or about 0.3 mmol / g or more, or about 2.0 mmol / g or less, or about 1.5 mmol / g or less.
[0116] If the surface acidity is too low or too high, a problem of increased impregnation with the electrolyte may occur.
[0117] The binder composition for secondary batteries may have an electrolyte impregnation of about 200% or less. Here, the electrolyte impregnation refers to the volume increase of a dry film when the binder composition is prepared into a dry film and then immersed in an electrolyte at about 25° C. for about 48 hours. In this case, the electrolyte may be an alkylene carbonate-based electrolyte, more specifically, a mixed electrolyte of ethylene carbonate / propylene carbonate / propyl propionate (mixed volume ratio of EC / PC / PP=3 / 1 / 6).
[0118] The electrolyte impregnation can have a lower limit of about 1% or more, alternatively about 10% or more, or alternatively about 30% or more, and an upper limit of about 200% or less, alternatively about 170% or less, alternatively about 150% or less, alternatively about 100% or less, or alternatively about 70% or less, thereby exhibiting a relatively low electrolyte impregnation.
[0119] solvent According to an embodiment of the present invention, the binder composition for a secondary battery may further include a solvent in addition to the emulsion polymer particles, i.e., the latex particles.
[0120] The substance used as the solvent or dispersion medium is not particularly limited, and examples thereof include water; alcohols such as methanol, ethanol, propanol, isopropanol, butanol, isobutanol, pentanol, isopentanol, and hexanol; ketones such as acetone, methyl ethyl ketone, methyl propyl ketone, cyclopentanone, and cyclohexanone; ethers such as methyl ethyl ether, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, diisobutyl ether, di-n-amyl ether, diisoamyl ether, methyl propyl ether, methyl isopropyl ether, methyl butyl ether, ethyl isoamyl ether, and tetrahydrofuran; lactones such as δ-butyrolactone, δ-butyrolactone; lactams such as β-lactam; cyclic aliphatics such as cyclopentane, cyclohexane, cycloheptane; aromatic hydrocarbons such as benzene, toluene, o-xylene, m-xylene, p-xylene, ethylbenzene, propylbenzene, isopropylbenzene, butylbenzene; aliphatic hydrocarbons such as heptane, octane, nonane, decane; linear and cyclic amides such as dimethylformamide, N-methylpyrrolidone; esters such as methyl lactate, ethyl lactate, propyl lactate, butyl lactate, methyl benzoate; and the like. Among these, it is preferable to use a dispersion medium having a boiling point of 80°C or higher, preferably 85°C or higher, in terms of the process.
[0121] In this regard, the solvent may be used in an amount of about 50 to about 1,000 parts by weight, preferably about 100 to about 300 parts by weight, based on 100 parts by weight of the latex particles in terms of stability and viscosity control of the latex particles. For example, the solvent may be used in such an amount that the total solid content (TSC) is controlled to about 5 to about 70% by weight based on the total weight of the binder composition.
[0122] If too little solvent is used, the stability of the latex particles may be reduced, whereas if too much solvent is used, the viscosity may be reduced, weakening the coating properties, resulting in a reduction in the overall performance of the battery.
[0123] Electrode mixture and electrode Meanwhile, according to another aspect of the present invention, there is provided a secondary battery electrode mixture comprising the above-mentioned binder composition for secondary batteries and an electrode active material.
[0124] According to yet another aspect of the present invention, there is provided a secondary battery electrode including an electrode mixture layer containing such a secondary battery electrode mixture; and an electrode current collector.
[0125] Except for the binder, the electrode active material and electrode current collector used in the electrode mixture and electrode of the present invention may each contain generally known components.
[0126] For example, the electrode mixture can be used to manufacture a negative electrode, i.e., the electrode mixture can be a negative electrode mixture, and the electrode active material can be a negative electrode active material.
[0127] Here, the binder may be included in an amount of 1 wt% to 10 wt%, specifically 1 wt% to 5 wt%, based on the total weight (100 wt%) of the negative electrode mixture. When this is satisfied, the content of the negative electrode active material can be relatively increased, and the discharge capacity of the electrode can be further improved.
[0128] Meanwhile, since the binder has excellent properties in terms of binding strength, mechanical properties, and the like, not only when a graphite-based negative electrode active material is used as the negative electrode active material of the negative electrode mixture, but also when a negative electrode active material having a higher capacity is used, the binder can maintain the binding strength between the negative electrode active materials, between the negative electrode active material and the negative electrode current collector, and the like, and can suppress the expansion of the negative electrode active material due to its own mechanical properties.
[0129] As described above, since the binder is suitable for use not only with the graphite-based negative electrode active material but also with a negative electrode active material having a higher capacity, the type of the negative electrode active material is not particularly limited in one embodiment of the present invention.
[0130] Specifically, examples of the negative electrode active material include carbon and graphite materials such as natural graphite, artificial graphite, carbon fiber, and graphitizable carbon; metals such as Al, Si, Sn, Ag, Bi, Mg, Zn, In, Ge, Pb, Pd, Pt, Ti that can form an alloy with lithium, and compounds containing such elements; composites of metals and their compounds with carbon and graphite materials; lithium-containing nitrides; titanium oxides; lithium titanium oxides, etc., but are not limited thereto. Among them, carbon-based active materials, silicon-based active materials, tin-based active materials, or silicon-carbon-based active materials are more preferable, and these can be used alone or in combination of two or more.
[0131] Here, the carbon-based active material is one or more substances selected from the group consisting of natural graphite, artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch, mesophase pitch-based carbon fiber, carbon microspheres, petroleum or coal-based coke, softened carbon, and hardened carbon exemplified above. And the silicon-based active material is a compound containing Si, that is, Si, Si-C composite, SiO x (0 < x < 2), the Si-Q alloy, mixtures thereof, or mixtures of at least one of these with SiO 2 can be included.
[0132] The negative electrode current collector is generally made to a thickness of 3 to 500 μm. Such a negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, like the positive electrode current collector, fine irregularities can be formed on the surface to strengthen the binding force of the negative electrode active material, and it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0133] The negative electrode is manufactured by applying an electrode mixture containing a negative electrode active material and the binder onto a negative electrode current collector, followed by drying and rolling. If necessary, a conductive material, a filler, etc. may be further added to the negative electrode.
[0134] The conductive material is not particularly limited as long as it does not induce a chemical change in the battery but has conductivity, and examples of the conductive material that can be used include graphite such as natural graphite and artificial graphite; carbon black such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and summer black; conductive fibers such as carbon nanotubes, carbon fibers, and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.
[0135] The filler is a component that suppresses the expansion of the negative electrode, is used selectively, and is not particularly limited as long as it does not induce chemical changes in the battery and is a fibrous material. For example, fibrous materials such as olefin polymers such as polyethylene and polypropylene; glass fibers, and carbon fibers can be used.
[0136] Meanwhile, the electrode mixture is not limited to use for a negative electrode, and may also be used for manufacturing a positive electrode, that is, the electrode mixture may be a positive electrode mixture, and the electrode active material may be a positive electrode active material.
[0137] The positive electrode active material is a layered compound such as lithium cobalt oxide (LiCoO 2 ), lithium nickel oxide (LiNiO 2 ), or a compound substituted with one or more transition metals; a lithium manganese oxide such as a chemical formula Li 1+x Mn 2-x O 4 (where x is 0 to 0.33), LiMnO 3 , LiMn 2 O 3 , LiMnO 2 ; lithium copper oxide (Li 2 CuO 2 ); vanadium oxides such as LiV 3 O 8 , LiFe 3 O 4 , V 2 O 5 , Cu 2 V 2 O 7 ; a lithium iron phosphate system represented by a chemical formula Li 1+a Fe 1-x M x PO 4-b A b (where M is any one or more selected from the group consisting of MN, Ni, Co, Cu, Sc, Ti, Cr, V, and Zn, A is any one or more selected from the group consisting of S, Se, F, Cl, and I, -0.5 < a < 0.5, 0 ≤ x < 0.5, 0 ≤ b ≤ 0.1); a Ni-site type lithium nickel oxide represented by a chemical formula LiNi 1-x M x O 2 (where M = Co, Mn, Al, CuFe, Mg, B, or Ga, and x = 0.01 to 0.3); a chemical formula LiMn 2-x M x O 2 (where M = Co, Ni, Fe, Cr, Zn, or Ta, and x = 0.01 to 0.1), Li 2 Mn 3 MO 8Lithium manganese composite oxide represented by (where M = Fe, Co, Ni, Cu or Zn) or LiNi x Mn 2-x O 4 Spinel-structured lithium manganese composite oxide; chemical formula Li(Ni p Co q Mn r1 )O 2 Lithium-nickel-manganese-cobalt-based oxide represented by (where 0 < p < 1, 0 < q < 1, 0 < r1 < 1, p + q + r1 = 1), or Li(Ni p1 Co q1 Mn r2 )O 4 Lithium-nickel-manganese-cobalt-based oxide represented by (where 0 < p1 < 2, 0 < q1 < 2, 0 < r2 < 2, p1 + q1 + r2 = 2, etc.), or Li(Ni p2 Co q2 Mn r3 M s2 )O 2 Lithium-nickel-cobalt-transition metal (M) oxide represented by (where M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg and Mo, and p2, q2, r3 and s2 are atomic fractions of independent elements, 0 < p2 < 1, 0 < q2 < 1, 0 < r3 < 1, 0 < s2 < 1, p2 + q2 + r3 + s2 = 1), etc., but not limited thereto.
[0138] The positive electrode current collector is generally made to have a thickness of 3 to 500 μm. Such a positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery but has high conductivity. For example, stainless steel, aluminum, nickel, titanium, fired carbon, or those obtained by surface treatment of the surface of aluminum or stainless steel with carbon, nickel, titanium, silver, etc. can be used. The current collector can also form fine irregularities on its surface to enhance the adhesive force of the positive electrode active material, and various forms such as films, sheets, foils, nets, porous bodies, foams, non-woven fabrics, etc. are possible.
[0139] Of the negative electrode and the positive electrode, the electrode not using the binder described above may use a commonly known binder, representative examples of which include, but are not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc.
[0140] The negative electrode and the positive electrode may be manufactured by mixing an active material and a binder, and optionally a conductive material and a filler, in a solvent to prepare a slurry-like electrode mixture, and then coating the electrode mixture on each electrode current collector. Such an electrode manufacturing method is widely known in the art, and therefore a detailed description thereof will be omitted in this specification.
[0141] battery According to another aspect of the present invention, there is provided a secondary battery including the secondary battery electrode. Specifically, the battery may include a positive electrode, an electrolyte, and a negative electrode.
[0142] The secondary battery may be a lithium secondary battery.
[0143] The lithium secondary battery may be manufactured by impregnating an electrode assembly including a positive electrode, a separator, and a negative electrode with a non-aqueous electrolyte.
[0144] The positive electrode and the negative electrode are as described above.
[0145] Specifically, the negative electrode may include at least one negative electrode active material selected from the group consisting of carbonaceous materials and silicon compounds.
[0146] The separator separates the negative electrode and the positive electrode and provides a passage for lithium ions to move, and any separator that is commonly used in lithium batteries can be used. That is, a separator that has low resistance to the movement of electrolyte ions and has excellent electrolyte humidification ability can be used. For example, the separator can be selected from glass fiber, polyester, Teflon, polyethylene, polypropylene, polytetrafluoroethylene (PTFE), or a combination thereof, and can be in the form of a non-woven or woven fabric. For example, polyolefin-based polymer separators such as polyethylene and polypropylene are mainly used in lithium ion batteries, and coated separators containing ceramic components or polymer materials can also be used to ensure heat resistance or mechanical strength, and can be selectively used in a single-layer or multi-layer structure.
[0147] In some cases, a gel polymer electrolyte may be coated on the separator to improve the safety of the battery. Representative examples of such gel polymers include polyethylene oxide, polyvinylidene fluoride, polyacrylonitrile, etc.
[0148] However, when a solid electrolyte is used instead of the nonaqueous electrolyte, the solid electrolyte can also serve as the separator.
[0149] The non-aqueous electrolyte may be a liquid electrolyte including a non-aqueous organic solvent and a lithium salt, the non-aqueous organic solvent serving as a medium through which ions involved in the electrochemical reaction of the battery can move.
[0150] As the non-aqueous electrolyte, a non-aqueous electrolytic solution, an organic solid electrolyte, an inorganic solid electrolyte, or the like is used.
[0151] As the non-aqueous electrolyte, for example, aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, 4-methyl-1,3-dioxene, diethyl ether, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ether, methyl propionate, and ethyl propionate can be used.
[0152] As the organic solid electrolyte, for example, polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, polyagitation lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, polymers containing ionic dissociation groups, and the like can be used.
[0153] The inorganic solid electrolyte may be, for example, Li 3 N, LiI, Li 5 NI 2 , Li 3 N-LiI-LiOH, LiSiO 4 , LiSiO 4 -LiI-LiOH, Li 2 SiS 3 , Li 4 SiO 4 , Li 4 SiO 4 -LiI-LiOH, Li 3 PO 4 -Li 2 S-SiS 2 Nitrides, halides, sulfates, etc. of Li such as those mentioned above can be used.
[0154] The lithium salt is a substance that is easily dissolved in the non-aqueous electrolyte, and is, for example, LiCl, LiBr, LiI, LiClO 4 , LiBF 4 , LiB 10 Cl 10 , LiPF 6 , LiCF 3 SO 3 , LiCF 3 CO 2 , LiAsF 6 , LiSbF 6 , LiAlCl 4 , C.H. 3 SO 3 Li, C.F. 3 SO 3 Li, LiSCN, LiC(CF 3 SO 2 ) 3 , (CF 3 SO 2 ) 2 NLi, lithium chloroborane, lithium lower aliphatic carboxylate, lithium 4-phenylborate, etc. can be used.
[0155] In addition, for the purpose of improving charge / discharge characteristics, flame retardancy, etc., the electrolyte may contain, for example, pyridine, triethyl phosphate, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, aluminum trichloride, etc. In some cases, in order to impart non-flammability, a halogen-containing solvent such as carbon tetrachloride or ethylene trifluoride may be further added, carbon dioxide gas may be further added to improve high-temperature storage characteristics, or FEC (fluoro-ethylene carbonate), PRS (propene sultone), FPC (fluoro-propylene carbonate), etc. may be further added.
[0156] The lithium secondary battery according to the present invention can be used not only in a battery cell used as a power source for a small device, but also in a unit battery for a medium- to large-sized battery module including a large number of battery cells. Effect of the Invention
[0157] The binder composition for a secondary battery according to the present invention has excellent properties such as binding strength and mechanical properties, and can maintain the structural stability of an electrode even during repeated charge-discharge cycles, thereby improving the performance of a secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0158] The functions and effects of the present invention will be described in more detail below through specific examples of the present invention. However, these examples are merely presented as examples of the present invention and do not define the scope of the invention.
[0159] <Example 1> Determination of aggregate content The aggregate content of the binders obtained in the following Examples and Comparative Examples was measured by the following method.
[0160] 300 g of water was added to 100 g of the binder obtained in the following Examples and Comparative Examples, and a mixer (Eurostar 40, manufactured by IKA) was used to fix the head so that it was immersed in the binder, and shear was applied at 150 rpm for about 10 minutes, and then the mixture was removed and filtered through a 200 mesh sieve, and the amount of coagulum remaining on the sieve was measured.
[0161] The content of the measured aggregates was calculated in ppm units based on the weight of the binder to be measured.
[0162] In general, when the content of agglomerates before neutralization is less than 1000 ppm, and when the content of agglomerates after neutralization is less than 100 ppm, it is evaluated as good.
[0163] Measurement of electrolyte impregnation The electrolyte impregnation ability of the binders obtained in the following Examples and Comparative Examples was measured by the following method.
[0164] 20 g of the binder obtained in the following examples and comparative examples was applied to the surface of a rectangular mold that had been subjected to a contouring treatment, and then dried at 25°C for 24 hours and then at 80°C for 24 hours, and then peeled off to prepare a film. This was cut into a rectangular specimen with a long horizontal length, and the exact horizontal length was measured. (Ma)
[0165] The film after the length measurement was completed was immersed in about 15 g of electrolyte at 25° C. for 48 hours, and the horizontal length of the immersed specimen was measured. (Mb)
[0166] At this time, the electrolyte was prepared by mixing ethylene carbonate / propylene carbonate / propyl propionate (mixing volume ratio of EC / PC / PP=3 / 1 / 6).
[0167] The electrolyte impregnation was calculated according to the following formula 1. [Formula 1] Electrolyte impregnation (%) = ((Mb / Ma) 3 -1) x 100
[0168] Particle size measurement 0.02 g of the binder obtained in the following examples and comparative examples was diluted with 20 g of distilled water, and the average particle size (Di) was measured using a particle size measuring device (NICOMP380, Entegris).
[0169] Preparation of emulsion polymer particles with core-shell structure Example 1: Production Example 1: First Polymerization (Core Formation) As monomers for forming the core, 50 g of 1,3-butadiene, 35 g of styrene, 10 g of methyl methacrylate, and 5 g of a mixture of acrylic acid and itaconic acid in a ratio of 5:5 were used.
[0170] As a solvent, about 400 parts by weight of water was used per 100 parts by weight of the total monomer components.
[0171] Water, the monomers, and about 3 parts by weight of sodium lauryl sulfate as an emulsifier component per 100 parts by weight of the total monomer components were added to a nitrogen-substituted polymerization reactor, and the temperature was raised to about 75°C. Then, 0.005 mol of potassium persulfate was added as a polymerization initiator to start emulsion polymerization.
[0172] The polymerization reaction was carried out for about 7 hours while maintaining the temperature at about 75° C., to obtain a binder in the form of an emulsion.
[0173] Production Example 2: Second Polymerization (Shell Formation) As additional monomers for forming the shell, 74.9 g of n-butyl acrylate, 15 g of styrene, 10 g of methacrylic acid, and 0.1 g of allyl methacrylate were used, and 933.3 g (233.33 g based on solid content) of the emulsion polymer particles obtained in Preparation Example 1 was used.
[0174] Approximately 105 g of water was used as the solvent.
[0175] Into a polymerization reactor purged with nitrogen, water, the monomer, the latex particle cores of Preparation Example 1, and about 0.2 parts by weight of sodium polyoxyethylene lauryl ether sulfate as an emulsifier component relative to 100 parts by weight of the total monomer components were added, and while maintaining the temperature at about 80°C, 0.33 parts by weight of ammonium persulfate as a polymerization initiator relative to 100 parts by weight of the monomer components was added to start emulsion polymerization.
[0176] The reaction was carried out for about 5 hours while maintaining the temperature at about 80° C., to obtain an emulsion-type binder containing emulsion polymer particles with a core-shell structure (average particle size: 73 nm; aggregate content: 130 ppm; electrolyte impregnation: 167%).
[0177] The pH was adjusted to 6 using an aqueous sodium hydroxide solution (aggregate content after neutralization: 10 ppm).
[0178] Example 2: In the second polymerization, 69.9 g of n-butyl acrylate, 30 g of methacrylic acid, and 0.1 g of allyl methacrylate were used as monomers, and the same procedure as in Example 1 was carried out to obtain an emulsion-type binder containing emulsion polymer particles having a core-shell structure. (Average particle size: 78 nm; aggregate content before neutralization: 900 ppm; aggregate content after neutralization: 40 ppm; electrolyte impregnation: 95%)
[0179] Example 3: In the second polymerization, 59.9 g of n-butyl acrylate, 40 g of methacrylic acid, and 0.1 g of allyl methacrylate were used as monomers, and the same procedure as in Example 1 was carried out to obtain an emulsion-type binder containing emulsion polymer particles having a core-shell structure. (Average particle size: 101 nm; aggregate content before neutralization: 550 ppm; aggregate content after neutralization: 60 ppm; electrolyte impregnation: 29%)
[0180] Comparative Example 1: As monomers, 64.9 g of n-butyl acrylate, 25 g of styrene, 10 g of methacrylic acid, and 0.1 g of allyl methacrylate were used.
[0181] As the solvent, about 90 g of water was used.
[0182] Water, the monomers, and about 0.8 parts by weight of sodium polyoxyethylene lauryl ether sulfate and about 0.4 parts by weight of sodium dodecyl diphenyl ether disulfonate as emulsifier components relative to 100 parts by weight of the total monomer components were charged into a nitrogen-substituted polymerization reactor, and while maintaining the temperature at about 80°C, 0.85 parts by weight of ammonium persulfate as a polymerization initiator relative to 100 parts by weight of the monomer components was charged to start emulsion polymerization.
[0183] The reaction was carried out for about 8 hours while maintaining the temperature at about 80° C., to obtain an emulsion-type binder containing acrylate-based emulsion polymer particles (average particle size: 123 nm; aggregate content: 30 ppm; electrolyte impregnation: 523%).
[0184] The pH was adjusted to 6 using an aqueous sodium hydroxide solution (aggregate content after neutralization: 90 ppm).
[0185] Comparative Example 2: A binder in the form of an emulsion containing acrylate-based emulsion polymer particles was obtained in the same manner as in Comparative Example 1, except that 60 g of n-butyl acrylate, 20 g of styrene, and 20 g of methacrylic acid were used as monomers. (Average particle size: 118 nm; aggregate content before neutralization: 150 ppm; aggregate content after neutralization: 210 ppm; electrolyte impregnation: 446%)
[0186] Comparative Example 3: Preparation of polyacrylic acid aqueous solution (C) As the monomer, 100 g of acrylic acid was used.
[0187] Water and the monomers were added to a nitrogen-purged polymerization reactor, and while maintaining the temperature at about 80°C, 0.16 parts by weight of ammonium persulfate per 100 parts by weight of the monomer component was added as a polymerization initiator to initiate polymerization.
[0188] The reaction was carried out for about 5 hours while maintaining the temperature at about 80° C., to obtain a binder (C) in the form of an aqueous solution.
[0189] The pH of the obtained polyacrylic acid polymer aqueous solution (C) was adjusted to 7 using sodium hydroxide. (Agglomerate content: 0 ppm; electrolyte impregnation: 0%)
[0190] Comparative Example 4: Production Example 3: First Polymerization (Core Formation) As monomers for forming the core, 51.5 g of 1,3-butadiene, 36.5 g of styrene, 10 g of methyl methacrylate, and 2 g of a mixture of acrylic acid and itaconic acid in a ratio of 5:5 were used.
[0191] As a solvent, about 400 parts by weight of water was used per 100 parts by weight of the total monomer components.
[0192] Water, the monomers, and about 3 parts by weight of sodium lauryl sulfate as an emulsifier component per 100 parts by weight of the total monomer components were added to a nitrogen-substituted polymerization reactor, and the temperature was raised to about 75°C. Then, 0.005 mol of potassium persulfate was added as a polymerization initiator to start emulsion polymerization.
[0193] The polymerization reaction was carried out for about 7 hours while maintaining the temperature at about 75° C., to obtain a binder in the form of an emulsion.
[0194] Production Example 4: Second Polymerization (Shell Formation) As additional monomers for forming the shell, 74.9 g of n-butyl acrylate, 21.4 g of styrene, 4 g of methacrylic acid, and 0.1 g of allyl methacrylate were used, and 933.3 g (233.33 g based on solid content) of the emulsion polymer particles obtained in Preparation Example 3 was used.
[0195] Approximately 115 g of water was used as the solvent.
[0196] Into a polymerization reactor purged with nitrogen, water, the monomer, the latex particle cores of Preparation Example 3, and about 0.5 parts by weight of sodium polyoxyethylene lauryl ether sulfate as an emulsifier component relative to 100 parts by weight of the total monomer components were added, and while maintaining the temperature at about 75°C, 0.35 parts by weight of potassium persulfate as a polymerization initiator relative to 100 parts by weight of the monomer components was added to start emulsion polymerization.
[0197] After all the monomers and initiators were added, the temperature was maintained at about 80°C and the reaction was carried out for about 5 hours to obtain an emulsion-type binder containing emulsion polymer particles with a core-shell structure (average particle size: 75 nm; aggregate content: 10 ppm; electrolyte impregnation: not measurable).
[0198] The pH was adjusted to 6 using an aqueous sodium hydroxide solution (aggregate content after neutralization: 10 ppm).
[0199] Manufacture of negative electrode mixture Using water as a dispersion medium, 81.2 g of artificial graphite, 14.3 g of silicon oxide, 1.0 g of acetylene black, 2.3 g of the binder prepared above, and 1.2 g of carboxymethyl cellulose as a thickener were mixed based on 100 g of total solids, to prepare a slurry for the negative electrode so that the total solids content was 42 wt%.
[0200] Anode production The negative electrode mixture was applied to a copper foil to a thickness of about 130 μm using a comma coater, dried in a dry oven at 80° C. for 10 minutes, roll-pressed to a final thickness of 95 μm, and then dried in a vacuum oven at 120° C. for 12 hours to obtain a negative electrode.
[0201] Electrode Adhesion Test In order to measure the adhesive strength between the electrode mixture and the current collector, the surface of each of the electrodes manufactured in the examples and comparative examples was cut and fixed to a slide glass, and then the current collector was peeled off and the 180 degree peel strength was measured.
[0202] Three measurements were taken for each electrode and the average was calculated.
[0203] Measurement of electrode detachment amount Each of the electrodes manufactured in the Examples, Reference Examples, and Comparative Examples was punched out using a punching machine (31 mm x 43 mm), and the presence or absence of material generated by detachment on the side surface was confirmed. If no detachment occurred, it was rated as good, and if detachment occurred, it was rated as poor.
[0204] Measurement of surface acidity and the ratio of repeating units derived from unsaturated carboxylic acid monomers present on the surface of emulsion polymer particles (direct conductometric titration) To the binder in emulsion form containing 1 g of solids was added 5 ml of 0.05 M aqueous hydrochloric acid solution.
[0205] Using direct conductometric titration, the change in electrical conductivity was measured while dropping 0.05M NaOH aqueous solution to calculate the number of moles of carboxyl groups distributed on the surface of the latex particles, from which the weight of repeating units derived from unsaturated carboxylic acid monomers distributed on the surface of the latex particles was calculated, and the weight was expressed as a percentage (wt%) of the total weight of the latex particles including the core and shell.
[0206] The specific experiments and calculation principles are summarized in the following paper: (Journal of Applied Polymer, volume 23, issue 3, February 1, 1979, pp. 893-901)
[0207] The measurement results are summarized in the table below.
[0208] [Table 1]
[0209] It can be clearly seen from Table 1 that the electrolyte impregnation is less in the examples than in the comparative examples. Therefore, it is believed that when the binders of the examples are applied to secondary batteries, electrode expansion during repeated charge and discharge can be effectively suppressed.
[0210] In Examples 2 and 3, it can be clearly seen that although the acid content on the particle surface is relatively high compared to Comparative Example 2, there is little generation of agglomerates during the neutralization stage. When the ratio of unsaturated carboxylic acid monomer is extremely high as in Comparative Example 3, the electrolyte impregnation is improved to some extent, but the adhesive strength is reduced and detachment occurs on the side of the coated electrode.
[0211] For reference, in Comparative Example 4, the surface acidity value was too low and the content of the repeating unit derived from the unsaturated carboxylic acid monomer relative to the total particle weight was too low, so that the particles could not maintain a good shape and collapsed during the measurement of the electrolyte impregnation, making it impossible to measure.
Claims
1. The emulsion polymer particles include core-shell structured emulsion polymer particles. the core of the emulsion polymer particle contains, relative to 100 parts by weight of repeating units derived from a conjugated diene monomer, 50 to 100 parts by weight of repeating units derived from an aromatic vinyl monomer, 5 to 50 parts by weight of repeating units derived from an alkyl (meth)acrylate monomer, and 1 to 20 parts by weight of repeating units derived from an unsaturated carboxylic acid monomer; the shell of the emulsion polymer particle contains 5 to 100 parts by weight of a repeating unit derived from an unsaturated carboxylic acid monomer and 5 to 70 parts by weight of a repeating unit derived from an aromatic vinyl monomer, based on 100 parts by weight of an alkyl (meth)acrylate repeating unit; The emulsion polymer particles have a relative content of repeating units derived from an unsaturated carboxylic acid monomer of 5 wt % or more based on the total weight including the core and the shell, a weight ratio of the repeating units derived from the unsaturated carboxylic acid monomer present on the surface of the emulsion polymer particles to the total weight of the emulsion polymer particles is 2 wt % or more; The emulsion polymer particles satisfy the following relational formula 1 and have a surface acidity value of 0.3 to 2.0 mmol / g: Binder composition for secondary battery electrodes: [Relationship 1] AC-Core<AC-Shell In the above formula, AC-Core is the relative content (wt%) of the repeating unit derived from the unsaturated carboxylic acid monomer in the core of the emulsion polymer particle, and AC-Shell is the relative content (wt%) of the repeating unit derived from the unsaturated carboxylic acid monomer in the shell of the emulsion polymer particle.
2. The binder composition for a secondary battery electrode according to claim 1, which satisfies the following relational formula 2: [Relationship 2] 2×AC-Core<AC-Shell In the above formula, AC-Core is the relative content (wt%) of the repeating unit derived from the unsaturated carboxylic acid monomer in the core of the emulsion polymer particle, and AC-Shell is the relative content (wt%) of the repeating unit derived from the unsaturated carboxylic acid monomer in the shell of the emulsion polymer particle.
3. The binder composition for a secondary battery electrode according to claim 1 , wherein the shell of the emulsion polymer particle includes a crosslinked bond formed by a crosslinking agent.
4. The binder composition for a secondary battery electrode according to claim 3 , wherein the crosslinking agent is a compound containing both an acryloyl group and an ethylenically unsaturated bond in a molecule.
5. A binder composition for secondary battery electrodes as described in claim 1, wherein the electrolyte impregnation property represented by the following mathematical formula 1 is 200% or less. [Formula 1] Electrolyte impregnation (%)=((Mb / Ma) 3 −1)×100 In the above formula 1, Ma is the width of a specimen obtained by applying 20 g of binder to the surface of a rectangular mold that has been subjected to a contouring treatment, sequentially drying the applied binder at 25° C. for 24 hours and at 80° C. for 24 hours, peeling the applied binder off, and cutting the specimen into a rectangular shape with a longer width, and Mb is the width of the specimen that has been immersed in about 15 g of electrolyte at 25° C. for 48 hours.
6. 6. The binder composition for a secondary battery electrode according to claim 1, wherein the surface acidity value of the emulsion polymer particles is 0.3 to 1.5 mmol / g.
7. A secondary battery electrode binder composition according to any one of claims 1 to 6 and an electrode active material, Secondary battery electrode mixture.
8. The secondary battery electrode mixture according to claim 7 , further comprising a conductive material.
9. An electrode mixture layer comprising the secondary battery electrode mixture according to claim 7 or 8; and Includes an electrode current collector; Secondary battery electrode.
10. A secondary battery comprising the secondary battery electrode according to claim 9.
11. The secondary battery according to claim 10 , comprising one or more negative electrode active materials selected from the group consisting of carbon-based active materials and silicon-based active materials.
Citation Information
Patent Citations
Binder composition for secondary cell electrode, slurry composition for secondary cell electrode, secondary cell electrode, and secondary cell
KR1020160110363A
Binder composition for secondary-battery electrode, slurry composition for secondary-battery electrode, secondary-battery electrode, and secondary battery
KR1020170053615A
Binder composition for secondary-battery electrode, slurry composition for secondary-battery electrode, secondary-battery electrode, and secondary battery
WO2016035286A1
Binder composition for electricity storage devices, slurry composition for electricity storage device electrodes, electrode for electricity storage devices, and electricity storage device
WO2019208419A1
Slurry composition for nonaqueous secondary battery functional layers, separator for nonaqueous secondary batteries, and nonaqueous secondary battery
WO2020175025A1